Karakteristik dan Keterampilan Pramusaji di Era Revolusi Industri 4.0 pada Hotel The Oberoi Beach Resort Bali - Gita, Gede Elga Krisna; Mahardika, Yudha M.; Widiastini, Ni Made Ary (Jurnal Manajemen Perhotelan dan Pariwisata, 2020)
This study aimed to finding the characteristics and skills of waiters in the era of the industrial revolution 4.0 on The Oberoi Beach Resort Bali. This research was a qualitative descriptive study, using observation and interviews as a method of collecting data. Subject of the study were drawn from Hotelier in the field of governance and HRD. In addition to foreign language skills, good communication, there are additional skills and characteristics in the revolutionary era 4.0 found in this study are 4 characteristics (technological literacy, following developments in the field of governance, being able to work efficiently and effectively and mastering technology and systems) and 4 skills (following the times, can use new tools related to operational work, follow the latest service trends and understand the system and computers) waiters in the era of the industrial revolution 4.0. In the future, it was expected that there will be studies that discuss the same topic in order to study more sources and references related to the characteristics and skills of waiters in the 4.0 era, so that they get better and more complete results.